INVENTARISASI TUMBUHAN ANGGREK DI KAWASAN SUAKA MARGASATWA SIRANGGAS KABUPATEN PAKPAK BHARAT (INVENTORY OF ORCHIDS IN SIRANGGAS WILDLIFE PAKPAK BHARAT) - Dasma Banurea; Yunasfi Yunasfi; Pindi Patana (Peronema Forestry Science Journal, 2015)
Indonesia's tropical forests is one of the richest in natural resources of orchids. North Sumatra is a suitable place for growing orchids. This study aims to inventory the orchids based on altitude in Siranggas Wildlife Kecupak I Village, Pergetteng-getteng Sengkut Subdistrick, Pakpak Bharat. Plots were determined by purposive sampling. The Observation of vegetation used line plot transect which divided in 3 locations with different altitude interval : 800 – 900 meter above sea level (m asl), 1.000 – 1.100 m asl and  1.200 – 1.300 m asl, measuring plot 20 m x 100 m, divided in to 5 subplots measuring 20 m x 20 m. The result found 54 species of orchids at Siranggas Wildlife from 21 genus, which there were 15 species of terrestrial orchids, 37 species of epiphytic orchids and 2 species os saprophyte. The highest of important value index (IVI) was 41,722% on Dendrobium tertraedre and the lowest was 0,884% on Vanilla sp. 1, Vanilla sp. 3 and Phaius sp 1. Keywords: Orchid, Inventory, Siranggas Wildlife